FFT - Based Watermarking for Copyright Protection of Color Image - Joshua Febrian Wiranata; Sri Redjeki Pudjaprasetya; Pritta Etriana Putri; Riski Kurniawan (Journal of Applied Mathematics and Modelling, 2025)
Watermarks are commonly used by authors to prevent unauthorized copying and to protect their intellectual property. When a watermark is applied to a digital image, it is expected that the watermark will not be visible, and the watermark will retain its good quality when extracted. This paper is focused on one type of color image watermarking method, using the Fast Fourier Transform (FFT) algorithm. In this algorithm, the watermark is embedded in the frequency domain of the image. In this way, our watermark algorithm exhibits good quality and demonstrates strong resistance against common attacks. Here, we experimented with compression, blur, object addition, and noise addition.